2007
DOI: 10.1158/1078-0432.ccr-07-0895
|View full text |Cite
|
Sign up to set email alerts
|

Association of Intratumoral Vascular Endothelial Growth Factor Expression and Clinical Outcome for Patients with Gastrointestinal Stromal Tumors Treated with Imatinib Mesylate

Abstract: Purpose: Imatinib mesylate (imatinib) has revolutionized clinical outcomes of patients with advanced gastrointestinal stromal tumor (GIST). However, the degree of individual benefit varies, and little is known about prognostic factors for these patients. Importantly, selected patients may be treated with an approach to target both Kit and vascular endothelial growth factor receptor (VEGFR) expression. Experimental Design: Using tissue microarray technology, we analyzed 53 imatinib-naive GISTs for vascular endo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…Moreover, vaccination against cancer-specific antigens can sensitize the tumor against subsequent chemotherapeutic treatment (38-43). Our data bring up the first evidence of (a) a host-derived factor in dictating GIST outcome during IM therapy (3,44,45), of (b) a prognostic effect of NK cell functions in solid tumors, and of (c) an immunologic ''off-target'' effect on NK cells of a tyrosine kinase inhibitor. A larger patient series will be needed to validate the prognostic value of an augmented NK cell IFN-g production at 2 months of IM therapy and to establish the added value of this immunologic parameter over that of the c-kit mutation status or ultrasonography (46).…”
Section: Discussionmentioning
confidence: 58%
“…Moreover, vaccination against cancer-specific antigens can sensitize the tumor against subsequent chemotherapeutic treatment (38-43). Our data bring up the first evidence of (a) a host-derived factor in dictating GIST outcome during IM therapy (3,44,45), of (b) a prognostic effect of NK cell functions in solid tumors, and of (c) an immunologic ''off-target'' effect on NK cells of a tyrosine kinase inhibitor. A larger patient series will be needed to validate the prognostic value of an augmented NK cell IFN-g production at 2 months of IM therapy and to establish the added value of this immunologic parameter over that of the c-kit mutation status or ultrasonography (46).…”
Section: Discussionmentioning
confidence: 58%
“…In a small study by Wang et al, serum vascular endothelial growth factor (VEGF) levels were higher in the high-risk GIST patients [10]. Another study showed a positive correlation between high VEGF expression and poor survival independent by KIT genotype [11]. All of our patients enrolled, previously received the antiangiogenesis agent, SU.…”
Section: Discussionmentioning
confidence: 66%
“…There was a trend toward better outcomes for patients with wild-type KIT or exon 11 mutation compared with exon 9 mutation, although this was not statistically significant. In addition to tumor genotype, other molecular markers such as vascular endothelial growth factor [25] or Bcl-2 [26] expression have been suggested to correlate with survival in GIST patients treated with imatinib. The role of these biomarkers in Korean patients compared with those from western populations also needs to be explored further.…”
Section: Discussionmentioning
confidence: 99%